A holistic approach to requirements elicitation for mobile tourist recommendation systems - Gregoriades, Andreas; Pampaka, Maria; Georgiades, Michael (My University, 2019)
Mobile recommendation systems (MRS) are becoming ever more popular in the tourism industry, due to their potential to declutter the decision-making process of tourists. Despite their proliferation, such systems seem to lack accuracy and relevance to the needs of their users. This paper describes the mobile recommendation problem and explores the relationships between personality, emotion, context and recommendations for tourists. Its aim is to investigate user-requirements of prospective mobile recommendation systems for tourists and the influence of personality and emotional state on user needs. To that end, a survey was conducted with tourists in Cyprus at a point of interest to identify their recommendation needs. Collected data have been analyzed and preliminary results indicate different user requirements among contextual factors. This indicated that the contextualization of these applications in accordance with users’ personality and emotional state is essential to realize their full potential.
Keywords: Context; Emotion; Mobile recommendation systems; Personality; User requirements